2019
DOI: 10.1029/2019jd031238
|View full text |Cite
|
Sign up to set email alerts
|

Radar Reflectivity of Lightning Flashes in Stratiform Regions of Mesoscale Convective Systems

Abstract: A total of 254 flashes observed in 14 mesoscale convective systems in Chongqing, China, during the summers of 2014–2015 was used to investigate the characteristics of lightning flashes in stratiform regions (stratiform lightning flashes). The data were analyzed and combined with data from an S‐band Doppler radar system. The results show that the reflectivity characteristics of stratiform lightning flashes are different from those of convective lightning flashes. More than 90% of the stratiform lightning flashe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 51 publications
0
10
0
Order By: Relevance
“…Therefore, it is reasonable to infer that some in‐situ electrifications contribute to the formation of the charge structures in the stratiform regions or strengthening of these charge layers (Bateman et al., 1995; Engholm et al., 1990; Rutledge & Peterson, 1993; Rutledge et al., 1990; Stolzenburg et al., 1994). The close relationship between the stratiform lightning flashes initiated or propagating near the melting level and the bright band (Wang et al., 2018, 2019) indicates that some electrification mechanisms associated with the microphysical processes near the melting level (Dinger & Gunn, 1946; Drake & Mason, 1966; Williams, 2018; Zheng et al., 2019) may evidently influence the lower charge layers in the stratiform regions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is reasonable to infer that some in‐situ electrifications contribute to the formation of the charge structures in the stratiform regions or strengthening of these charge layers (Bateman et al., 1995; Engholm et al., 1990; Rutledge & Peterson, 1993; Rutledge et al., 1990; Stolzenburg et al., 1994). The close relationship between the stratiform lightning flashes initiated or propagating near the melting level and the bright band (Wang et al., 2018, 2019) indicates that some electrification mechanisms associated with the microphysical processes near the melting level (Dinger & Gunn, 1946; Drake & Mason, 1966; Williams, 2018; Zheng et al., 2019) may evidently influence the lower charge layers in the stratiform regions.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, we will try to use the dataset of 254 lightning flashes initiated in 14 MCSs in Chongqing, China, which has been used for analysis by Wang et al. (2018, 2019) to explore the horizontal extent of lightning channels, especially channels propagating in positive charge layers, in stratiform regions. Based on the results of the analysis, we can find out more about the characteristics of the horizontal areas of these positive charge layers participating in discharges in the stratiform region and discuss their possible mechanisms.…”
Section: Introductionmentioning
confidence: 99%
“…The lightning flashes used for analysis in this study were located by a network consisting of 14 sensors (Figure 1) that received the very-high-frequency (VHF) signals radiated by lightning, located in Chongqing, southwest China [6,17,18]. This lightning mapping system was similar in design to the lightning mapping array used in the United States [19][20][21][22].…”
Section: Data 21 Lightning Location Datamentioning
confidence: 99%
“…The reflectivity of cloud-to-ground lightning flashes at initiation has been found to be stronger than that of intra-cloud lightning flashes [4,8]. Moreover, recent research has shown that the reflectivity characteristics of stratiform initiation regions of lightning flashes in MCSs are different from those initiated in convective regions [6]. In other regions, some researchers have used data from similar lightning location systems to analyze the characteristics of lightning flashes, including intra-cloud and cloud-to-ground lightning flashes, combined with radar data, and derived similar results for the distributions of lightning initiation/propagation altitude and co-located radar variation [8][9][10][11].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation